Sistem Pakar Untuk Diagnosis Penyakit Ayam Dengan Menggunakan Metode Certainty Factor (CF) Berbasis Web - Eva Itma Anna; budi hartanto (Jurnal Teknologi dan Informatika (JEDA), 2021)
Abstract Currently, expert systems are widely used in various fields, one of which is the use of expert systems in the field of animal health such as chickens. In the world of chicken farming, every farmer, both small scale and large scale, pays attention to the health of chickens, where health will affect profits. However, many of the community breeders find it quite difficult to get information about livestock problems, such as the process of recognizing quickly and accurately, it is difficult to detect the types of diseases that are caused which are generally similar and the same and there are other difficulties because there are other things so they are reluctant to come to the veterinarian. Based on these constraints, the authors propose an expert system software engineering system to determine chicken disease using certainty factor methods. This system can help in determining a decision and providing more accurate information, because system decisions not only rely on rules, but also generate probability and percentage values using certainty factor methods so that it is easier for small scale breeders and can save time and costs as well as It makes it easier for users to recognize the types of diseases, especially those caused by viruses and bacteria, because the system user only selects the symptoms that appear on the consultation page and after that a decision of the disease and its solution will appear.